Titanium Dioxide Nanoparticles and Sodium Nitroprusside Alleviate the Adverse Effects of Cadmium Stress on Germination and Seedling Growth of Wheat (Triticum aestivum L.) - Faraji, Javad (2018)
Effect of titanium dioxide nanoparticles (TiO2 NPs) (0, 500, 1 000 and2 000 mg/L) and sodium nitroprusside (SNP) (0 and 100 M) as nitricoxide (NO) donor, on wheat seed germination and seedling growthwere investigated under cadmium (Cd) stress (0, 50 and 100 mM CdCl2).Concentration-dependent declining trends were observed in wheatgermination indices upon seed exposure to CdCl2 suspensions whichwere more obvious under higher Cd stress. Exogenous sodium nitroprusside (SNP) and TiO2 nanoparticles (NPs) positively affected most germination indices under normal and stress conditions. In most cases, combined application of TiO2 NPs and SNP suspensions boosted stimulatory function of both compounds and moderated adverse effects of Cd treatments on wheat seed germination and seedling growth. 2 000 mg/L TiO2 + SNP (100 M) treatment recorded the best results regarding most germination indices under lower and higher (50 and 100 mM CdCl2) Cd stress. Overall, it could be concluded that application of TiO2 NPs in combination with SNP might be a promising approach in counteracting the adverse effects of Cd stress on wheat seed germination and early growth.